Stochastic Simulation of Strong Ground Motions From Two M > 5 Uttarakhand Earthquakes - Sharma, Nitin; Srinagesh, D.; Suresh, G.; Srinivas, D. (Frontiers in Earth Science, 2021)
Many studies based on geodetic data and statistical analysis of seismicity have pointed out that sufficient amount of stress accumulated in the Himalayan plate boundary may host a big earthquake. Consequently, high seismic activities and infrastructural developments in the major cities around Himalayan regions are always of major concern. The ground motion parameter estimation plays a vital role in near real time evaluation of potential damaged areas and helps in mitigating the seismic hazard. Therefore, keeping in mind, the importance of estimation of ground motion parameters we targeted two moderate size earthquakes occurred recently within a gap of 10 months in Uttarakhand region with M>5.0 on 06/02/2017 and 06/12/2017. The ground motions are simulated by adopting stochastic modeling technique. The source is assumed as ω-2 circular point source (Brune’s model). The average value of reported anelastic attenuation from various studies, the Quality factor, Qs =130.4*(f0.996) and stress drop values obtained through iterative procedure are considered for simulations. The stochastic spectra is generated between 0.1 and 10 Hz of frequency range. The site effect is also estimated by using H/V method in the same frequency range. The synthetic spectra are compared with the observed Fourier amplitude spectra obtained from recorded waveform data and converted back to the time histories. The stochastic time histories compared with observed waveforms and discussed in terms of amplitude (PGA). The simulated and observed response spectra at different structural periods is also discussed. The mismatch between observed and simulated PGA values along with the GMPE exist for shallow crustal earthquakes is also discussed in the present work.